Traditional food choices of Malaysian university students: social influence, preferences and health - Zainudin, Aiza Nur Syahmina; Jamaludin, Hanis Nazirah; Sulong, Siti Nurhanifah; Idris, Nur Amanina; Ideris, Muhamad Shah Kamal (Faculty of Hotel and Tourism Management, Universiti Teknologi MARA Selangor, Puncak Alam Campus, 2025)
Traditional food selection among university students is increasingly influenced by modern lifestyles and global food trends, raising concerns about the diminishing role of traditional cuisine in the lives of younger generations. The present study investigates the factors and relationship between social influence, food preferences and health factor among Faculty of Hotel and Tourism Universiti Teknologi MARA (UiTM) students. An online survey administered among students generated 356 valid responses. The analyses consisted of descriptive analysis and Regression analysis. The findings highlight that food preferences and health considerations are the main reasons students choose traditional food, while social influence plays a lesser role. In addition, these results reflect the shifting food culture among younger generations, where enjoyment and health perception are becoming central to food choices. This study also contributes to the literature by showing that health and taste outweigh cultural pressures in shaping student traditional food choices.